The Development of Plant Breeding Educational Game (GEMPITA) to Enhance Grade IV Students’ Critical Thinking Skills - Akhlilia, Tudrika; Tri Joko Raharjo; Harianingsih (Papanda Publisher, 2025)
Critical thinking skills development remains a significant challenge in Indonesian elementary education, particularly in science subjects where traditional teaching methods often fail to engage students effectively. This study aimed to develop and evaluate GEMPITA (Plant Breeding Educational Game) to enhance Grade IV students' critical thinking skills through an integrated Problem-Based Learning approach. The research employed a Research and Development methodology using the ADDIE model. The study was conducted at SD Negeri Palebon 03 Semarang City with 34 Grade IV students across two implementation phases: small-scale trial (6 students) and large-scale trial (28 students). Data collection included expert validation, instrument validity testing, and one-group pretest-posttest experimental design. Statistical analysis employed normality testing, paired sample t-tests, and N-Gain calculations to assess learning effectiveness. Expert validation achieved 91-93% approval ratings across material, media, and language criteria. The assessment instrument demonstrated high reliability (r = 0.95) with 34 valid items from 50 initial questions. Both implementation phases showed significant improvement in critical thinking skills, with mean scores increasing from 51-53 to 90 points. Learning completeness improved dramatically from 0% to 96-100%. N-Gain analysis revealed high effectiveness (0.80) in both trials, with statistically significant differences (p < 0.05) between pretest and posttest scores. Student response rates reached 96-97%, indicating excellent acceptance. GEMPITA effectively enhanced critical thinking skills through game-based learning integration with Problem-Based Learning methodology. The findings support theoretical frameworks of problem-based learning and socio-conflict theories while providing practical evidence for technology-enhanced pedagogical approaches in Indonesian elementary education contexts.